KEBIJAKAN RESENTRALISASI PERTAMBANGAN DAN IMPLIKASINYA TERHADAP TATA KELOLA PERTAMBANGAN RAKYAT DI KABUPATEN LEBAK - Fuad, Anis; Dewi, Shanty Kartika; Mahpudin, Mahpudin; Yadia, Putri Khispa (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
The amendment of Indonesia’s Mineral and Coal Law through Law No. 3 of 2020 has significantly reshaped the governance of the mining sector. A key feature of the new regulation is the re-centralization of authority, whereby licensing power was withdrawn from local governments and concentrated at the national level. The central problem arising from this shift is the increasing marginalization of small-scale and traditional miners, whose operations persist under illegal status due to overlapping regulations and conflicting interests among levels of government. This study investigates the implications of the new mining regulatory framework by examining the case of illegal gold mining in Lebak Regency, Indonesia. In this region, local communities have long relied on traditional gold mining as a survival strategy amid poverty and the absence of alternative livelihoods, despite the illegality of such practices. Employing a qualitative case study approach, based on literature review and interviews with key informants, the findings reveal ongoing contestation over resource control between government, corporations, and local miners. The state tends to favor large-scale corporate mining, leaving traditional miners marginalized and criminalized.